2023
DOI: 10.3389/fpubh.2023.1086771
|View full text |Cite
|
Sign up to set email alerts
|

The triglyceride glucose-waist-to-height ratio outperforms obesity and other triglyceride-related parameters in detecting prediabetes in normal-weight Qatari adults: A cross-sectional study

Abstract: IntroductionThe triglyceride-glucose (TyG)-driven indices, incorporating obesity indices, have been proposed as reliable markers of insulin resistance and related comorbidities such as diabetes. This study evaluated the effectiveness of these indices in detecting prediabetes in normal-weight individuals from a Middle Eastern population.MethodsUsing the data of 5,996 adult Qatari participants from the Qatar Biobank cohort, we employed adjusted logistic regression to assess the ability of various obesity and tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…We used triglyceride indices as analytical tools for our linear regression analysis to further elucidate the relationship between sAAa and cardiovascular risk with greater precision. The formulas utilized to compute these indices were as in our previous publication ( 22 ). The disparities in these indices between male and female subjects are presented in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used triglyceride indices as analytical tools for our linear regression analysis to further elucidate the relationship between sAAa and cardiovascular risk with greater precision. The formulas utilized to compute these indices were as in our previous publication ( 22 ). The disparities in these indices between male and female subjects are presented in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Triglyceride glucose (TyG)-related parameters (TyG), TyG–Body mass index (TyG-BMI), TyG-WC, and TyG-WHTR were calculated using the formulas from Al Akl et al. ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, triglyceride-based markers are also associated with NAFLD and other inflammatory and metabolic disorders such as hypertension, 32 cardiovascular conditions, 33 and T2DM. 34 However, there is limited research on the relationship between the TyG index and NAFLD. A study involving 10,761 healthy Chinese adults found that the TyG index could serve as a promising diagnostic tool for NAFLD in this population, with an optimal cut-off value of 8.5 (AUC = 0.782).…”
Section: Discussionmentioning
confidence: 99%
“…We obtained cross-sectional clinical, anthropometric, and demographic data of 5996 Qatari individuals aged between 18 and 86 years (3,229 Females and 2,771 Males) from Qatar Biobank (QBB), a national institute running a well-phenotyped cohort, by collecting data from the general population in Qatar since 2012 [19]. Based on the American Diabetes Association guidelines, 1996 (33.2%) of the 5996 subjects had prediabetes, de ned as having HbA1 c levels between 39 mmol/mol (5.7%) and 47 mmol/mol (6.4%).…”
Section: Study Populationmentioning
confidence: 99%
“…Test of equality of ROC areas between LR and all the other ML algorithms this study of relatively normal-weight Qatari adults, Triglyceride which is known to be one of the risk factors for diabetes has been found to be an indicator associated with prediabetes[19]. Our data analyses underscored that prediabetes is not all about obesity and lipid concentration, and triglyceride may be an additional biomarker for screening individuals at high risk for prediabetes in this population One of the strengths of our study is the large sample size.…”
mentioning
confidence: 99%